RESOLUTION OF A RACEMIC ISOLEUCINE MIXTURE BY USING METHYL L-MANDELATE - Rani Maharani; Ace Tatang Hidayat; Dadan Sumiarsa; Achmad Zainuddin; Ika Wiani Hidayat (Chimica et Natura Acta, 2016)
A methyl ester of L-mandelic acid was found to be an effective resolving agent for resolution of commercial DL-isoleucine. The resolution was based on Steglich esterification between methyl L-mandelate and Boc-DL-isoleucine. The two resolved isomers were easily separated by using a conventional flash-column chromatography, giving quantitatively good yields. Unfortunately, the methyl L-mandelate was found to be ineffective to resolve four stereoisomers of Fmoc- isoleucine.